Construction of an infectious cloning system of porcine reproductive and respiratory syndrome virus and identification of glycoprotein 5 as a potential determinant of virulence and pathogenicity - Wei, Yuqing; Dai, Guo; Huang, Mei; Wen, Lianghai; Chen, Rui Ai; Liu, Ding Xiang (Frontiers in Microbiology, 2023)
Porcine reproductive and respiratory syndrome virus (PRRSV) infection of pigs causes a variety of clinical manifestations, depending on the pathogenicity and virulence of the specific strain.Identification and characterization of potential determinant(s) for the pathogenicity and virulence of these strains would be an essential step to precisely design and develop effective anti-PRRSV intervention. In this study, we report the construction of an infectious clone system based on PRRSV vaccine strain SP by homologous recombination technique, and the rescue of a chimeric rSP-HUB2 strain by replacing the GP5 and M protein-coding region from SP strain with the corresponding region from a highly pathogenic strain PRRSV-HUB2. The two recombinant viruses were shown to be genetically stable and share similar growth kinetics, with rSP-HUB2 exhibiting apparent growth and fitness advantages. Compared to in cells infected with PRRSV-rSP, infection of cells with rSP-HUB2 showed significantly more inhibition of the induction of type I interferon (IFN-β) and interferon stimulator gene 56 (ISG56), and significantly more promotion of the induction of proinflammatory cytokines IL-6, IL-8, ISG15 and ISG20. Further overexpression, deletion and mutagenesis studies demonstrated that amino acid residue F16 in the N-terminal region of the GP5 protein from HUB2 was a determinant for the phenotypic difference between the two recombinant viruses. This study provides evidence that GP5 may function as a potential determinant for the pathogenicity and virulence of HP-PRRSV.